Employment relations and perceived organizational performance: the moderating role of technological intensity. Issue 1 (3rd September 2020) - , Harsh; Prasad, Asha
Abstract : Purpose: The purpose of the study is to examine the relationship of different dimensions of employment relation (ER) with perceived organizational performance. The study also attempts to analyze the role of technological intensity in determining the employment approaches adopted by the firm. Design/methodology/approach: Data were gathered through the survey method and in-depth personal interviews were conducted in Indian manufacturing firms based in the National Capital Region (NCR). Findings: The findings confirm that all dimensions of employment relation have profound and significant relationship with perceived organizational performance. It also revealed that technology intensity of the industry determines the way people are managed in the organization. Originality/value: The study has contributed to the existing body of knowledge by understanding the impact of unique framework of ER (industrial relations and HRM) on organizational performance. The study represents the one of the fewest attempts to measure technology intensity as moderating variable in ER & Performance.